THE THYMUS GLAND (THYMUS) ASPECTS IN CHILDREN (PART VI). ASPECTS OF TREATMENT AND PREVENTION OF "THYMUS-MEDIATED" (to a certain extent) PATHOLOGICAL CONDITIONS - Юрий Иванович Ровда; Наталья Николаевна Миняйлова; Алена Владимировна Ведерникова; Иван Константинович Халивопуло; Андрей Владимирович Шабалдин; Анна Андреевна Лобыкина; Ольга Валерьевна Шмакова; Сергей Фадеевич Зинчук; Наталья Степановна Черных; Владислав Викторович Сохарев; Яна Вячеславовна Юнкина (The Publishing House Medicine and Enlightenment, 2022)
Studies of drugs that affect the T-cell link of immunity, which began in the middle of the 20th century, continue without losing relevance even now. There have been many attempts in the medical community to create drugs from thymus extracts that have a peptide base. Some of which - «thymalin», «thymosin», «tactivin», are used at the present time, though with a narrower range of indications. Gone is the era of the use of these drugs, for example, in immunosuppression of hematopoiesis, in primary immunodeficiency states, in the treatment of acute septic and purulent-inflammatory pathologies, in frequently and long-term ill children (with combined thymomegaly), etc. This was facilitated by the development of new diagnostic technologies that prove the multicomponent nature of the regulatory structures of the immune system, which cannot be fully squeezed into the Procrustean bed of the action of only thymic peptides. But in recent years, positive results have been obtained using these drugs in patients with COVID-19, and with acquired immunodeficiency syndrome (AIDS), as well as in the treatment of lymphocytopenia in an infant. In addition to thymus peptides, the use of growth hormone (GH) is proposed, which acts as a stimulator of thymus stromal cells. In different countries of the world, research is being conducted aimed at preventing thymus involution, ways to restore the thymus gland are being considered: from the use of Korean red ginseng to progenitor cell transplantation. In addition, active work is underway in an attempt to create an artificial thymus based on thymus cells embedded in nanofibers. Currently, hundreds of types of primary immunodeficiencies (PID) have been identified, new diagnostic methods and markers have been improved and discovered, which has made it possible to overestimate the role of thymomegaly and microthymus in the origin of immunodeficiency in children, although the facts of increased morbidity (often viral etiology) in young children with data bipolar states of the thymus are difficult to dispute, especially when the subsequent long-term follow-up of these children was not seriously subjected to scientific analysis. And if we take into account the position that the clinical manifestation of a primary immunodeficiency state is possible at any age, then the presence of critical thymomegaly or microthymus (even transient) at an early age can be the "first signs" of this syndrome, which will clinically manifest itself much later, then, when the processes of age-related involution of the VJ are added to this. In any case, this category of children requires further study and close attention of scientists in order to develop modern methods of diagnosis and treatment.